How I treat heterozygous hereditary antithrombin deficiency in pregnancy - Bramham, Kate; Retter, Andrew; Robinson, Susan E.; Mitchell, Michael; Moore, Gary W.; Hunt, Beverley J. (Thrombosis and Haemostasis, 2013)
Untreated hereditary antithrombin deficiency in pregnancy is associated with maternal venous thromboembolism (VTE) and possibly with fetal loss. Thromboprophylaxis during pregnancy is recommended, but dosages remain controversial. Our objective was to perform a retrospective assessment of thrombotic events and pregnancy outcomes in women with hereditary antithrombin deficiency managed according to a standard protocol. Pregnancies in individuals with hereditary antithrombin deficiency were identified from a hospital database. Women with no prior VTE received enoxaparin 40 mg daily until 16 weeks gestation and thereafter 40 mg twice daily. Women with prior VTE received intermediate dose enoxaparin (1 mg/kg) once daily, increased to twice daily at 16 weeks and anti-Xa monitored dosing. Thromboprophylaxis was stopped at initiation of labour or 12 hours prior to caesarean and 50 IU/kg antithrombin concentrate given. Thromboprophylaxis was restarted after delivery. Eighteen pregnancies in 11 women with antithrombin deficiency were identified. Seventeen pregnancies (94%) were successful. Median gestation was 39 weeks (range 30–41) and median birth-weight was 2,995 g (910–4,120 g),but 6/17 infants (35%) were small for gestational age (p=0.01). Estimated blood loss at delivery was median 375 ml (200–600 ml). Four pregnancies were complicated by VTE; one newly presented with a thrombotic event, two patients were not taking thromboprophylaxis and one occurred despite thromboprophylaxis. Two novel mutations(p.Leu317Ser and p.His33GInfsX32) are described. In conclusion, in antithrombin deficiency the use of low-molecular-weight heparin in pregnancy and puerperium with antithrombin concentrate predelivery was associated with successful pregnancy outcome; rates of VTE appear to be lower than previously reported, but remain elevated
Keywords: Hereditary antithrombin deficiency; pregnancy